Gender, pensions and income in retirement - Anne Nolan; Adele Whelan; Seamus McGuinness; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2019)
This research, funded by the Pensions Council, finds that Ireland has a gender pension gap of 35%. The gap is primarily driven by the fact that women are less likely to receive a private or occupational pension. The ESRI study examines the pension income of men and women, the driving factors behind the gender pension gap and income poverty in old age.
Keywords: 330